Análisis del impuesto a la renta y su incidencia económica en las sociedades constructoras de Manabí - Mendoza Vergara, Jesús Bladimir (2022)
The objective of this research was to analyze the payment of income tax to measure its economic impact on construction companies in Manabí, period 2016-2019. The focus of the study is to try to determine to what extent the payment of income tax affects in this case, the construction companies in Manabí, since usually the tax is paid in advance and these companies have to resort to third party sources of financing to be able to meet these obligations affecting liquidity and therefore profits. The conceptualizations related to the subject of study are found in a theoretical framework cited with their respective authors. Similarly, the methodological development has the respective types of research, which were bibliographic and field research, and the research methods were deductive, analytical, comparative, correlation and the Delphi method. The research techniques used were the survey, meta-analysis, Pearson's coefficient, Likert scale and Cronbach's alpha. Regarding the research tools, the questionnaire and the SPSS software were used to process and tabulate the information, obtaining the results and then analyzing them to issue the conclusions and recommendations of the research carried out